1994
DOI: 10.1111/j.1440-1819.1994.tb03076.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Interview Form to Estimate the Risk of Self‐Destructive Behaviors

Abstract: The authors devised the interview form, Schedule of Self‐Destructive Risks (SOS‐DR), for the estimation of risks of self‐destructive behaviors, and developed the subscale of SOS‐DR especially to estimate hopelessness as a potential risk to suicide. SOS‐DR had a favorable inter‐rater reliability shown by Intraclass Correlation Coefficient (ICC) and Kuder‐Richardson's alpha coefficient. On the basis of correlations of items in SOS‐DR with Beck Hopelessness Scale (BHS) in 52 patients, 18 items were selected and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The term equivalent to hopelessness in Japanese, "zetsubokan," is a fairly common word and is often used in everyday conversation. Studying 52 Japanese psychiatric patients, Ono, Murai, Yasuda, Nakamura, & Nakajima (1994) found that hopelessness was associated with suicidal tendency as well as depression. Despite these considerations, we are not aware of any investigations which studied hopelessness among a community population in Japan.…”
mentioning
confidence: 99%
“…The term equivalent to hopelessness in Japanese, "zetsubokan," is a fairly common word and is often used in everyday conversation. Studying 52 Japanese psychiatric patients, Ono, Murai, Yasuda, Nakamura, & Nakajima (1994) found that hopelessness was associated with suicidal tendency as well as depression. Despite these considerations, we are not aware of any investigations which studied hopelessness among a community population in Japan.…”
mentioning
confidence: 99%